The Influence of youth culture, self efficacy and peer influence on attitude towards sexual abstinence among university students (2009)
This study was designed to look at the role of youth culture, peer influence and self efficacy as it influences university students' sexual behaviour. Two hundred and forty (240) university undergraduates with the mean age of 24.32 years (60% males and 40% females were selected through purposive sampling technique. Self efficacy, peer group and youth culture were independently and significant joint predictors of attitude towards sexual abstinence (R2 = 0.40, F = (3,239), p <.0l). Self efficacy; peer group influence and youth culture interacted to influence sexual abstinence (F= (l, 239) = 3.765, p<.001). Students high on self efficacy and youth culture reported negative attitude towards sexual abstinence compared to those low on both self efficacy and youth culture other dyads of youth culture and self efficacy. Students high on Youth culture and peer influence also significantly reported negative attitude towards sexual abstinence (F= (l, 239) = 8.830, p<.001). The students high on self efficacy and peer influence reported negative attitude towards sexual abstinence compared to those low on both self efficacy and peer influence and other two dyads of peer influence and self efficacy (F= (1, 239) = 11.00, p<.001). Self efficacy, peer group influence and youth culture have significant influence on university sexual behaviour. The findings have implication for the design of intervention programmes such as peer counselling and referral services and educational programs for students on campus